An Activity of Flavonoid Derived Compounds from Medinilla speciosa Extract as Anti-hyperpigmentation against Tyrosinease Proteins with In Silico Methods - riantica, elshinta; Nurhayati, Awik Puji Dyah; Sa’adah, Noor Nailis (Universitas Nahdlatul Ulama Surabaya, 2024)
Parijoto (Medinilla speciosa), a typical plant from Indonesia, contains flavonoid compounds as antioxidants. It is able to depigment skin by inhibiting tyrosinase activity during melanogenesis, or melanin formation. Melanogenesis occurs through UV light exposure; it stimulates ROS production and triggers the formation of free radicals and melanogenesis. If not prevented, it will have negative impacts on health. Currently, there is no further research regarding the existence of flavonoid compound derivatives found in parijoto fruit. The aim of this research is to initially identify potential flavonoid derivative compounds as tyrosinase inhibitors using in silico methods. The results can be used as an initial reference for making products based on natural ingredients with minimal side effects. This research uses a bioinformatics approach with the molecular docking method of ligands towards proteins. The stages in this research include: downloading and preparing receptors and ligands; docking with Autodock Vina; visualization of results with Biovia Discovery Studio; data analysis; and discussion. The analysis is carried out by looking at the affinity energy values and complex conformation between the receptor-ligand. The results show flavonoid derivative compounds have the potential to act as tyrosinase inhibitors, as proven by compounds interactions with the active site of tyrosinase to produce the amino acid residues phenylalanine, proline, asparagine, arginine, and histamine. Produce respective affinity energy values, namely -8.9; -7.7; -7.6; -7.5; -7.5; and 7.4 kcal/mol for chalcone, catechin, flavonol, flavanol, flavone, and flavonone compounds. Meanwhile, the comparison compound used is kojic acid, with an affinity energy of -5.5 kcal/mol.